2016
DOI: 10.1016/s1474-4422(16)30234-4
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of minimally invasive surgery plus alteplase in intracerebral haemorrhage evacuation (MISTIE): a randomised, controlled, open-label, phase 2 trial

Abstract: SUMMARY Background Craniotomy, when evaluated in trials, does not improve outcome after intracerebral haemorrhage (ICH). Whether minimally invasive catheter evacuation followed by thrombolysis is safe and can achieve a good functional outcome by removing clot is unknown. We investigated safety and efficacy of alteplase with minimally invasive surgery (MIS) in patients with intracerebral haemorrhage. Methods MISTIE was an international, randomized, open-label study and was done in 26 hospitals in the USA, Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
396
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 378 publications
(422 citation statements)
references
References 35 publications
19
396
1
6
Order By: Relevance
“…The MISTIE phase II trial importantly showed no significant increase in symptomatic bleeding or infections in the surgical group and a trend towards improved functional outcomes with the surgical intervention. 23 For now, only conventional surgery is offered in the UK and existing data can help to guide patient selection.…”
Section: Neurosurgerymentioning
confidence: 99%
“…The MISTIE phase II trial importantly showed no significant increase in symptomatic bleeding or infections in the surgical group and a trend towards improved functional outcomes with the surgical intervention. 23 For now, only conventional surgery is offered in the UK and existing data can help to guide patient selection.…”
Section: Neurosurgerymentioning
confidence: 99%
“…Mortality reaches approximately 50% within the first 3 months and most survivors are left with severe disability (13). Despite major advances in the acute emergency neurological life support of patients with ICH, the optimal surgical management of these patients remains controversial (46). …”
mentioning
confidence: 99%
“…Because of this, multiple surgical approaches have been investigated with varying degree of success. Investigated procedures include conventional craniotomy, stereotactic guidance with aspiration and thrombolysis, image-guided stereotactic endoscopic aspiration, and decompressive craniectomy (46). …”
mentioning
confidence: 99%
See 2 more Smart Citations